Training tool for on-farm water management using heuristic simulation software - Shaban, Mohammed Z., author; Merkley, Gary P., author; U.S. Committee on Irrigation and Drainage, publisher (Colorado State University. Libraries, 2010)
A modern computer-based simulation tool in the form of a game for on-farm water management has been developed for application in training events for farmers, irrigators, irrigation extension specialists, and students. This training tool can be used to analyze both strategic and operational issues related to the management of on-farm water resources, and automatic analysis of the results to provide feedback to the trainees. It utilizes an interactive framework, thereby allowing the trainee (or player) to develop scenarios and test alternatives in a convenient, risk-free environment. It employs heuristic capabilities in a simulation approach for modeling all of the important aspects of on-farm water management that are essential to effective planning. The daily soil water balance, crop phenology, root development, and a seven-day weather forecast, can be monitored by the player throughout the simulated growing season. Different crop types, water delivery methods, and irrigation methods are made available to the player. Random events (both favorable and unfavorable) and different strategic decisions are included in the game for more realism and to provide potentially more challenging game play. Scoring and recommendations are provided at the end of the game, based on the management decisions made by the player.
Meeting irrigation demands in a water-challenged environment
Heuristic simulation software
Presented at Meeting irrigation demands in a water-challenged environment: SCADA and technology: tools to improve production: a USCID water management conference held on September 28 - October 1, 2010 in Fort Collins, Colorado.